MANAGERS’ PERSONALITY PREFERENCES, MANAGERIAL STYLES AND EMPLOYEE SATISFACTION OF MULTI-NATIONAL COMPANIES: AN INPUT TO HUMAN RESOURCE STRATEGIC PLAN - Buama, Chester Alexis C (PEOPLE: International Journal of Social Sciences, 2019)
This study determined the relationships that exist among managers’ personality preferences, management styles, and employees’ job satisfaction level. The study employed the descriptive-correlational method of research specifically the survey. The data were gathered through the questionnaires. It served as a survey tool to draw facts about managers’ personality preferences, management styles and employee’s level of job satisfaction. The respondents of the study were the managers from multi-national companies in the Province of Laguna. The researcher utilized the total enumeration of the respondents. They were composed of 65 managers and employees respectively. The study utilized two standardized test to measure the variables of the study. The null hypothesis stating that there is no significant relationship between the managers’ personality preferences and employee’s job satisfaction is rejected. Similarly, the null hypothesis stating that there is no significant relationship between the managers’ management styles and employee’s job satisfaction is also rejected.